2004
DOI: 10.1007/s00125-004-1612-3
|View full text |Cite
|
Sign up to set email alerts
|

Improved insulin sensitivity and adipose tissue dysregulation after short-term treatment with pioglitazone in non-diabetic, insulin-resistant subjects

Abstract: Aims/hypothesis: We examined whether shortterm treatment with a thiazolidinedione improves insulin sensitivity in non-obese but insulin-resistant subjects and whether this is associated with an improvement in dysregulated adipose tissue (reduced expression of IRS-1, GLUT4, PPARγ co-activator 1 and markers of terminal differentiation) that we have previously documented to be associated with insulin resistance. Methods: Ten nondiabetic subjects, identified as having low IRS-1 and GLUT-4 protein in adipose cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
74
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 60 publications
10
74
2
1
Order By: Relevance
“…Hammarstedt and colleagues treated non-diabetic insulin-resistant subjects with pioglitazone for 3 weeks and took adipose tissue biopsies before and after treatment [11]. In contrast to our findings, their study did not find any change in adipoR1 and R2 expressions in adipose tissue.…”
Section: Discussioncontrasting
confidence: 99%
“…Hammarstedt and colleagues treated non-diabetic insulin-resistant subjects with pioglitazone for 3 weeks and took adipose tissue biopsies before and after treatment [11]. In contrast to our findings, their study did not find any change in adipoR1 and R2 expressions in adipose tissue.…”
Section: Discussioncontrasting
confidence: 99%
“…Impaired expression of genes regulating adipogenesis, e.g. PPARG and sterol regulatory element binding transcription factor 1, has been shown to be related to insulin resistance [38] and treatment with thiazolidinediones improves insulin sensitivity in parallel with enhancing the differentiation of new, small adipocytes [11,39]. Other suggested mechanisms linking fat cell size and insulin resistance are alterations in the expression pattern of immune-related genes and an altered cholesterol balance in cellular membranes of enlarged adipocytes [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have demonstrated that the ratio of HMW to total adiponectin is more closely associated with glucose tolerance and insulin sensitivity than the plasma levels of total adiponectin (30,36,37). The HMW/total adiponectin ratio is decreased in obese subjects and in patients with T2DM and coronary heart disease, and this decrease is reversed following moderate weight reduction and treatment with thiazolidinediones (30,35,44). We (29) and others (26) have found that the sexual dimorphism of adiponectin in both humans and rodents is attributed primarily to the difference in the HMW adiponectin, with females having significantly higher levels of this oligomer compared with males.…”
Section: Discussionmentioning
confidence: 99%